The Portrayal of Marine Life in Chudori’s the Sea Speaks His Name - Mulatsih, Maria Vincentia Eka (Universitas Sanata Dharma, 2023)
Many countries in the world have experienced a massive movement. In Indonesia, one of them was the 1998 Indonesian student movement which was able to push Soeharto (Indonesian president at that time) to resign from his president position which had lasted for 32 years. This movement is narrated in a novel entitled The Sea Speaks His Name which is a translation work of an Indonesian novel entitled Laut Berbicara and is written by Leila S. Chudori. Laut Biru as the main character of this work took part in the 1998 Indonesian student movement and was drawn into an ocean as a result of his action. Interestingly, the portrayal of marine life and its surrounding is repeated several times in this work. Deploying difference and repetition theory of Delueze and reader-response approach, the researcher applied a closed reading method and wrote the analysis results descriptively. This study found that the portrayal of marine life and its surrounding tended to show the acceptance of Laut’s struggle to create a freedom in Indonesia. In this case, Chudori’s novel provided a different point of view that as a maritime country, the beauty of marine life and its surrounding had some important roles to convey the 1998 student movement in relation to love, struggle and setting.